Functional monosomy of 6q27‐qter and functional disomy of Xpter‐p22.11 due to X;6 translocation with an atypical X‐inactivation pattern. Issue 5 (31st March 2017) - Podolska, Anna; Kobelt, Albrecht; Fuchs, Sigrid; Hackmann, Karl; Rump, Andreas; Schröck, Evelin; Kutsche, Kerstin; Di Donato, Nataliya
Abstract : Pattern of X chromosome inactivation (XCI) is typically random in females. However, chromosomal rearrangements affecting the X chromosome can result in XCI skewing due to cell growth disadvantage. In case of an X;autosome translocation, this usually leads to an XCI pattern of 100:0 with the derivative X being the active one in the majority of females. A de novo balanced X;6 translocation [46, X, t(X;6)(p22.1;q27)] and a completely skewed XCI pattern (100:0) were detected in a female patient with microcephaly, cerebellar vermis hypoplasia, heart defect, and severe developmental delay. We mapped the breakpoint regions using fluorescence in situ hybridization and found the X‐linked gene POLA1 to be disrupted. POLA1 codes for the catalytic subunit of the polymerase α‐primase complex which is responsible for initiation of the DNA replication process; absence of POLA1 is probably incompatible with life. Consequently, by RBA banding we determined which of the X chromosomes was the active one in the patient. In all examined lymphocytes the wild‐type X chromosome was active. We propose that completely skewed XCI favoring the normal X chromosome resulted from death of cells with an active derivative X that was caused by a non‐functional POLA1 gene. In summary, we conclude that functional monosomy of 6q27‐qter and functional disomy of Xpter‐p22.11 are responsible for the clinical phenotype of the patient. This case demonstrates the importance of determining which one of the X chromosomes underwent inactivation to correlate clinical features of a female with an X;autosome translocation with the nature of the genetic alteration.